AVOIDING STEREOTYPING AND ENHANCING INTERCULTURAL UNDERSTANDING - Alistair Welsh (TEFLIN Journal: A publication on the teaching and learning of English, 2011)
Abstract: Anecdotally, language learners often struggle to acquire intercultural understanding. Teaching intercultural understanding presents significant challenges for language teachers. This article offers some in-sights into language learners intercultural understanding and strategies to help enhance intercultural understanding that seek to promote analytical and critical thinking. The aim is to build on the principles of the emerging pedagogy of Intercultural Language Learning (1cLL). IcLL suggests there is a third place, where cultures overlap. IcLL acknowledges the importance of identifying with the other, whilst not denying the self. Intercultural competence requires sensitivity to difference, an ability to identify with others and to critically reflect on ones own cultural background.